Penerapan Arsitektur Nusantara pada Masjid Agung Darul Muttaqin Batang - Aldi Setiawan (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
This study examines the application of Nusantara architecture in the Great Mosque of Darul Muttaqin, Batang, focusing on the multi-tiered limas roof as a representation of Javanese architectural identity in a contemporary mosque. The research addresses the dominance of Middle Eastern styles in modern mosque design in Indonesia, which may weaken local identity. Using a qualitative descriptive case study approach, data were collected through observation, visual documentation, and literature review. The results indicate that the multi-tiered limas roof functions structurally and climatically and conveys symbolic meanings related to spatial hierarchy and spirituality, affirming the relevance of Nusantara architecture today.